Using Spatial Econometrics to Analyze Local Growth in Sweden - Johan Lundberg (European Regional Science Association (ERSA), 2004)
This paper investigates factors that determine the average income growth and net migration rates in Swedish municipalities during the period 1981 to 1999. The main issue is to test the hypothesis that, conditional on a set of other possible determinants of regional growth, the growth rate in one municipality is affected by the growth rates in its neighboring municipalities. We also test the hypothesis of conditional convergence, that is, the hypothesis that initially 'poorer' regions tend to grow faster than initially 'richer' regions conditional on the other explanatory variables in the model. We find a positive correlation between net migration rates in neighboring municipalities, which suggests that net migration tend to 'spill over' to neighboring municipalities. When it comes to average income growth, our results indicate spatial dependence in the error terms during the 1980's. Such dependence is important in the sense that it indicates that shocks into the system not only affect the municipality where the shock has its origin but spread across the country. In addition, and in contrast to previous empirical findings based on Swedish data, we do not find any clear evidence in favour of the hypothesis of conditional convergence. Instead, our results predict conditional divergence between municipalities located in the Stockholm region throughout the period and also for municipalities outside the Stockholm region during the 1990's.
Keywords: 330